Chapter Saluti inaugurali. La Resistenza e il futuro - Smuraglia, Carlo (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper aims at showing the cultural and intellectual atmosphere the author brothe in the years of the Resistance movement. The author, who in that period was a partisan, vows that the Resistance movement will be studied in school in a way that show its capacities in stimulating youth trust in the future.